GREEN ACCOUNTING, ENVIRONMENTAL PERFORMANCE, AND PROFITABILITY: EMPIRICAL EVIDENCE ON HIGH PROFILE INDUSTRY IN INDONESIA - Eveline Viendra Tjoa; Luky Patricia Widianingsih (Research In Management and Accounting (RIMA), 2022)
This study aims to determine the effect of green accounting and environmental performance on the profitability of high-profile industry companies listed on the Indonesia Stock Exchange (IDX) for the 2017-2021 period. The company’s activities have a significant impact on the environment. A series of actions are needed to prevent further damage. On the other hand, financial aspects must also be considered when companies carry out social and environmental responsibilities. This needs to be done so that companies can maintain their sustainability. The independent variables of this study are green accounting and environmental performance. The dependent variable of this research is profitability. This study also uses a control variable, namely firm size. The population of this study is high-profile industry companies listed on the IDX in 2017-2021. Samples were taken using the purposive sampling method. The number of samples in this study was 69 companies with a total of 255 observation data. The data analysis technique used is multiple linear regression test with SPSS 25 program. The results of this study are green accounting does not affect profitability, environmental performance has a positive effect on profitability, and firm size has a negative effect on profitability.